POLITENESS STRATEGY FOUND IN THE 2014 PRESIDENTIAL CAMPAIGN OF ABURIZAL BAKRIE ADVERTISEMENTS - PAHLEVI, NOVIA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Politeness, Face Threatening Act, Politeness Strategy and AburizalBakrie.Language is a tool of communication and while communicating people need to know ”the rule” and one of which is politeness. One of important people who must be use politeness strategy is politicians. Nowadays, politician doing political campaign is by use advertisement as a tool to promote themself. There are two problems to be solved: (1) What face threatening acts are performed in the 2014 presidential campaign of Aburizal Bakrie advertisements? (2) What politeness strategies are performed to minimize the threat?. These problems are answered by using the theory of politeness strategy proposed by Brown and Levinson (1987).This study used qualitative approach in document analysis. The data were collected from 7 advertisement wich were shown on television from March 2013 until January 2014. In the form of transcript of the advertisement downloaded from www.youtube.com in March 2014The researcher found 18 utterances contain face threatening acts (FTA). Out of those utterances, 11 utterances contain negative FTA and 7 utterances contain positive FTA. The negative FTA are in the form orders and request, suggestion and advice, remaindings, promises, expressing thanks. The positive FTA are bringing a bad news or good news (boasting) about the speaker, increases or rising of dangerously emotional topics that relate to politics, race and religion and complimenting others. While in politeness strategies, the researcher found that 29 utterances containing positive politeness strategy which are; 1 notice-attend to the addresses, exaggerate, use in group identity markers, seek agreement, presuppose/raise/assert common ground, assert or presuppose the speaker’s knowledge of and concern for addressee’s wants, offer-promise, be optimistic, include both S&H in the activity and 3 give gifts to the hearer. The researcher did not find utterances contain negative politeness strategy. In this advertisements, the speaker mostly use negative face threatening act and positive politeness strategy to influence the hearer.It is very important for the people to know more closely about the personality of the speaker as president candidate and to be a smart elector after know what kind of face and politeness strategy that speaker shows. While for the the next researchers,who investigate the same area of study use another theory of politeness strategy and use another aspect of the object of advertisement for example advertisement on radio or text advertisement like billboard, magazine and newspaper.